1998
DOI: 10.1161/01.atv.18.9.1400
|View full text |Cite
|
Sign up to set email alerts
|

Warfarin Causes Rapid Calcification of the Elastic Lamellae in Rat Arteries and Heart Valves

Abstract: Abstract-High doses of warfarin cause focal calcification of the elastic lamellae in the media of major arteries and in aortic heart valves in the rat. Aortic calcification was first seen after 2 weeks of warfarin treatment and progressively increased in density at 3, 4, and 5 weeks of treatment. By 5 weeks, the highly focal calcification of major arteries could be seen on radiographs and by visual inspection of the artery. The calcification of arteries induced by warfarin is similar to that seen in the matrix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

28
449
2
13

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 497 publications
(492 citation statements)
references
References 45 publications
28
449
2
13
Order By: Relevance
“…MGP‐knockout mice developed soft‐tissue calcification resulting in vascular stiffening and died of vascular rupture 8 weeks after birth 16. Furthermore, both valvular and arterial calcification have been reported in animals on warfarin treatment 17. By contrast, limited data from experimental animal studies have indicated a potentially beneficial effect of novel, direct‐acting anticoagulants on the development and progression of atherosclerosis 18, 19, 20…”
Section: Discussionmentioning
confidence: 99%
“…MGP‐knockout mice developed soft‐tissue calcification resulting in vascular stiffening and died of vascular rupture 8 weeks after birth 16. Furthermore, both valvular and arterial calcification have been reported in animals on warfarin treatment 17. By contrast, limited data from experimental animal studies have indicated a potentially beneficial effect of novel, direct‐acting anticoagulants on the development and progression of atherosclerosis 18, 19, 20…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that the failure of some type I collagen structures to mineralize in vivo is due to the presence of powerful inhibitors of mineralization. Previous studies have shown that serum itself contains high levels of one potent inhibitor of hydroxyapatite formation, fetuin (a2-HS-glycoprotein) [28][29][30], and that the calcification of cartilage in vivo is normally prevented by the calcification inhibitory activity of the vitamin K-dependent matrix Gla protein [31,32]. It seems likely that type I collagen matrices that do not ordinarily calcify, such as tendon, contain other potent inhibitors of mineralization in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, vitamin K is an important regulator of bone and cartilage mineralization. Vitamin K also regulates growth plate cartilage calcification, as revealed by effects of vitamin K antagonism by warfarin (6)(7)(8)(9)(10). Genetic deficiencies of MGP in humans and mice have been linked to skeletal abnormalities, including premature epiphyseal calcification and shortening of long limb bones, reflecting endochondral bone formation (11)(12)(13)(14).…”
mentioning
confidence: 99%